Deterrence's Difficulty - Katyal, Neal Kumar (1997)
We all crave simple elegance. Physicists since Einstein have been searching for a grand unified theory that will tie everything together in a simple model. Law professors have their own grand theories - law and economics's Coase Theorem and constitutional law's Originalism immediately spring to mind. Criminal law is no different, for the analogue is our faith in deterrence - the belief that increasing the penalty on an activity will mean that fewer people will perform it. This theory has much to commend it. After all, economists and shoppers have known for ages that a price increase in a good means that people will consume less of it. But sometimes the consumption picture is more complicated than this simple economic account. Indeed, the leap from ordinary goods to criminal behavior is a large one, and one that presents complications of its own. This article sketches out several possible outcomes that arise from the criminalization of behavior. Incorporating recent work in economics, sociology, and psychology, it explains the ways in which the deterrence question is more difficult than many of us have assumed and illustrates how criminalization can create unintended, and sometimes perverse, incentives